Diminished synthesis of subunit a (ATP6) and altered function of ATP synthase and cytochrome c oxidase due to the mtDNA 2 bp microdeletion of TA at positions 9205 and 9206 - Jesina, Pavel; Tesarová, Markéta; Fornůsková, Daniela; Vojtísková, Alena; Pecina, Petr; Kaplanová, Vilma; Hansíková, Hana; Zeman, Jirí; Houstek, Josef (The Biochemical journal, 2004)
Dysfunction of mitochondrial ATPase (F1F(o)-ATP synthase) due to missense mutations in ATP6 [mtDNA (mitochondrial DNA)-encoded subunit a] is a frequent cause of severe mitochondrial encephalomyopathies. We have investigated a rare mtDNA mutation, i.e. a 2 bp deletion of TA at positions 9205 and 9206 (9205DeltaTA), which affects the STOP codon of the ATP6 gene and the cleavage site between the RNAs for ATP6 and COX3 (cytochrome c oxidase 3). The mutation was present at increasing load in a three-generation family (in blood: 16%/82%/>98%). In the affected boy with severe encephalopathy, a homoplasmic mutation was present in blood, fibroblasts and muscle. The fibroblasts from the patient showed normal aurovertin-sensitive ATPase hydrolytic activity, a 70% decrease in ATP synthesis and an 85% decrease in COX activity. ADP-stimulated respiration and the ADP-induced decrease in the mitochondrial membrane potential at state 4 were decreased by 50%. The content of subunit a was decreased 10-fold compared with other ATPase subunits, and [35S]-methionine labelling showed a 9-fold decrease in subunit a biosynthesis. The content of COX subunits 1, 4 and 6c was decreased by 30-60%. Northern Blot and quantitative real-time reverse transcription-PCR analysis further demonstrated that the primary ATP6--COX3 transcript is cleaved to the ATP6 and COX3 mRNAs 2-3-fold less efficiently. Structural studies by Blue-Native and two-dimensional electrophoresis revealed an altered pattern of COX assembly and instability of the ATPase complex, which dissociated into subcomplexes. The results indicate that the 9205DeltaTA mutation prevents the synthesis of ATPase subunit a, and causes the formation of incomplete ATPase complexes that are capable of ATP hydrolysis but not ATP synthesis. The mutation also affects the biogenesis of COX, which is present in a decreased amount in cells from affected individuals.
Keywords: Sequence Deletion; mitochondriální DNA; DNA, Mitochondrial; Membrane Potentials; RNA, Messenger; Mitochondria; adenosintrifosfát; sekvenční delece; Male; fibroblasty; mutace; Child, Preschool; adenosintrifosfatasy; Adenine; Fibroblasts; 2D gelová elektroforéza; adenin; Electrophoresis, Gel, Two-Dimensional; respirační komplex IV; mužské pohlaví; kůže; Mitochondrial Proton-Translocating ATPases; Thymidine; Electron Transport Complex IV; intracelulární membrány; membránové potenciály; spotřeba kyslíku; předškolní dítě; kultivované buňky; mitochondriální protonové ATPasy; Oxygen Consumption; lidé; Skin; Humans; Adenosine Triphosphatases; thymidin; Adenosine Triphosphate; Cells, Cultured; Mutation; Intracellular Membranes; messenger RNA; mitochondrie